Evaluation of Predisposing Risk Factors Among Patients with Cerebrovascular Accidents (Strokes) At Al- Bayda Medical Center - Mohammed, Fathia; Aisha Muhammed (Khalij-Libya Journal of Dental and Medical Research, 2023)
Background and Objective. The purpose of this study was to identify the relation between and different Cerebrovascular accidents (CVA) risk factors in AL Bayda Medical Center. Methods. A retrospective cross-sectional study of 170 (CVA) patients who were admitted to the medical ward of AL Bayda Medical Center from May 2022 to JUN 2023. The data was collected by reviewing hospital records for all admissions of CVA. Cases of transient ischemic attacks (TIA) were not included in the final analysis of the data due to uncertainty of diagnosis. Results. We included 170 cases of CVA excluding TIA. In regards of gender (61.7%) of the patients were male, females (38.2%), the difference was statistically significant (p=0.02). Mean age of male patients was 66.21±12.46 y and 67.77±11.85y for female patients, respectively, showing no significant difference statistically. Regarding the underlying causes of CVA, ischemic type was observed in 100 patients (58.8%), and the rest of the patients (41.1%) were hemorrhagic type. The most common presenting complaints were weakness of limbs in 130 cases (76.4%), altered mental status in 21 cases (12.4 %), headache, mouth angle deviation and slurring of speech in 19 cases (11.3%). The most common risk factor for stroke was hypertension in 99 patients (58.2%), smoking was the second most common modifiable risk factor in 79 patients (46.3%). Conclusion. Stroke is an amalgamate disease. The risk increasing with age and having male predominance. Hypertension was the most common risk factor and the most common type of stroke was ischemic stroke. These risk factors need an urgent program to reduce stroke morbidity and mortality.